The Pedagogical Ambassadorship Programme as an approach to academic development - Bolander Laksov, Klara (Högre utbildning, 2020)
In this article, the design of the Pedagogical Ambassadorship Programme at Stockholm University is examined. The aim of the programme is to assist departments in developing their educational culture by appointing a colleague as a pedagogical ambassador for one year. The programme was evaluated in a web survey to all ambassadors between 2015–2018.